Engineering nature : art & consciousness in the post-biological era - Ascott, Roy (Intellect, 2006)
This third volume in the Consciousness Reframed series, documenting the very latest artistic and theoretical research in new media and telematics including aspects of artificial life, robotics, technoetics, performance, computer music and intelligent architecture. The contributions to this volume represent the work produced at conferences and in journals which are only now emerging into more accessible literature. With over fifty highly respected practitioners and theorists in art and science contributing, there is a stimulating diversity of approach and a rich background of knowledge.